Keanekaragaman Jenis Burung Ekosistem Danau - Kasmiruddin Kasmiruddin; Tomi Hidayat; Sinta Yunita (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the diversity of bird species found in the Natural Tourism Park "Dendam Tak Sudah Lake" at Bengkulu City. The method used was direct survey in the field by exploring. The sampling was carried out by photographing and observing birds directly in the Natural Tourism Park "Dendam Tak Sudah Lake" at Bengkulu City. The data obtained were analyzed descriptively by looking at the morphology of the birds and identified based on reference books. The results showed that the birds found in the Natural Tourism Park "Dendam Tak Sudah Lake" were Collocalia esculanta, Halcyon smyrnensis, Streptopelia chinensis, Centropus bengalensis, Ardea cinerea, Ardea Purpurea, Ixobrychus cinnamomeus, Leptoptilos javanicus, Amaurphyrio procurornis, Procurornis. montanus, Pycnonotus goiavier, Lanius schach, Lonchura punculata and Lonchura maja. The index of bird species diversity at this location is H'= 2,413. In conclusion, the number of bird species found was 15 species from 11 families with a moderate diversity index. Keywords: Birds, Species Diversity, Natural Tourism Park "Dendam Tak Sudah Lake"